Spray cooling system for electronic cooling - Cheng, You Qin (2016)
Spray cooling has long been viewed as a conceivable method for cooling of electronic devices and researchers have long been trying to find the optimal parameters that can possibly maximise its thermal performance. In this present study, a closed-loop system was used to study the effects of different types of surfaces, different types of nozzles, different system pressure and also different spray orientation on spray cooling. The experiments were conducted under vacuum conditions so that the saturation temperature of water will boil lower than at atmospheric conditions. The study observed that thermal performance for 21mbar was in the range of 7.48% to 14.24% higher than that attained in 33mbar, hence showing that lower system pressure is more favourable for spray cooling performance. The study conducted experiments in both horizontal and vertical spray orientation and showed that the effects of spray orientations were minimal for both smooth plain surface and 0.5mm pin fins surface. However, horizontal spray orientation favours 0.5mm straight fins surface as compared to vertical spray orientation, with an improvement of 3.97% . The study also investigated the effects of enhanced surfaces, with the 0.5mm pin fins exhibited the best heat flux improvement of 13.10% relative to smooth plain surface. However, 0.5mm straight fins performed worse than smooth plain surface by 0.81%. By comparing the two enhanced surfaces, 0.5mm pin surface obtained 16.01% higher in thermal heat flux relative to 0.5mm straight fins at maximum heat flux of 649.55W/cm2. This is due to the lower fluid discharge velocities attributed to wider channels between the straight fins which result in poorer convective performance. The study also observed surface deposition on all surfaces, with smooth plain surface being the most prominent. Through its observation, characterisation of thermal resistances of the deposits were done. However, future studies will be needed to provide more comprehensive explanation for this phenomenon.